Incidence of ANA Positivity After the Administration of Biologicals - Manikandan Gopal; John Mathew (Journal of Clinical Rheumatology and Immunology)
Background: Antinuclear antibodies (ANA) are often used in diagnosing autoimmune rheumatological diseases, but their behavior in response to biological therapies, particularly in Asian patients, is not well-documented. The impact of these therapies on ANA status is crucial for understanding disease management and treatment efficacy. This study aims to evaluate the prevalence and significance of ANA positivity following the administration of biological agents in patients with autoimmune rheumatological diseases. Methods: This pilot study was a prospective cohort study involving 100 patients with autoimmune rheumatological diseases who were initially ANA negative at baseline. Predominantly included patients were axial spondyloarthritis (AxSpA) (n=95) and ANCA vasculitis (n=5). Patients with AxSpA were diagnosed according to the 2009 ASAS criteria, and treated with biological agents (e.g., TNF inhibitors such as adalimumab, etanercept, or IL-17 inhibitors such as secukinumab) and followed at a tertiary care center in India from January 2021 to December 2023. ANA levels were measured before and after 3, 6, 9, or 12 months of biological therapy. Changes in ANA positivity, clinical outcomes, and correlations with disease activity were analyzed. Results: Out of the 100 patients enrolled, 67 (67%) completed the study. All participants were ANA negative at baseline. After biological therapy, ANA positivity developed in 4 patients (5.9%). Despite this increase in Ana positivity, there was no significant correlation between ANA positivity and clinical disease activity, as measured by the Ankylosing Spondylitis Disease Activity Score (ASDAS) and the visual analog scale (VAS) for pain, BVAS suggesting effective therapeutic response despite changes in ANA status. Additionally, 30 patients were lost to follow-up, highlighting challenges related to the financial sustainability of biological therapy in the resource limited countries. Conclusion: Biological therapies for AxSpA are associated with an increase in ANA positivity although this change does not appear to impact clinical disease activity. The rise in ANA titres may reflect disease-related changes or treatment effects rather than a direct correlation with therapeutic efficacy. Further longitudinal studies are needed to understand the clinical significance of these findings and to refine the interpretation of ANA results during biological therapy.